Comparison of clinical presentation and outcome of neonatal SARS-COV2 during second wave from April-May 2021 and third wave from December 2021 to January 2022 in a tertiary care hospital in Eastern India - Ghoshal, Bhaswati; Andra, Akhila (International Journal of Contemporary Pediatrics, 2023)
Background: SARS-COV-2 manifestations in neonates acquired in the later part of neonatal life, were compared over 2 peaks over April-May 2021 (2nd wave) and (December 2021 to January 2022) (3rd wave). Setting: Study was done in Calcutta National Medical College, a tertiary care center of eastern India. Methods: Cross sectional study was done among the admitted neonatal cases in COVID designated NICU. Neonates acquired the COVID-19 infection after birth. All mothers were tested negative during delivery. Results: 40 neonates were admitted in April-May 2021 in COVID designated NICU and 42 neonates were admitted in December to January 2022. 66.6% mothers were COVID-19 RTPCR positive in December-January 2022 cases than 49.3% mothers in April-May 2021. These mothers were tested as COVID-19 negative at the time of delivery. None of the mothers were vaccinated in 2021 cases. Only 13.3% mothers received two doses of COVID-19 vaccination in December-January 2022 cases. Initial complaints were lethargic, not arousable (22.7%) and poor respiratory effort (27.5%) in December-January 22 cases. Respiratory (rapid breathing 40%) and gastrointestinal symptoms (diarrhoea 25.3%) were more predominant in neonates who were admitted in April-May 2021 than neonates who presented on January 2022. Hospital stay was significantly less in neonates in December-January 2022 (p=0.005). Genome sequencing revealed Omicron BA-2 in January 2022. Conclusions: Clinical presentations differ in neonates in April-May 2021 and December-January 2022 probably due to difference in the nature of the virus.